Trust as a Foundation for Ethical and Resilient Sharia Banking: Public Perception of Security and Reliability - febrika, Febrika sari; Sarmigi, Elex; Hj. Saini, Muhd. Zaki (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2025)
Purpose - This study aimed to analyze public perceptions of the security and reliability of transactions at Bank Syariah Indonesia (BSI), Sungai Penuh Branch. This research, informed by Trust Theory and the principles of maqāṣid al-sharī‘ah—specifically ḥifẓ al-māl (protection of money) and ḥifẓ al-‘ird (maintenance of dignity and social trust)—examines the impact of consumer confidence on the sustainability of Islamic banking. Method - The qualitative indicates that perceived security, reliability, and Shariah conformity substantially bolster trust in Islamic banking organizations. This trust, consequently, enhances client loyalty and adoption, so reinforcing the overarching governance and ethical goals of financial institutions. Findings - The analyze is expected to provide a comprehensive overview of how the public perceives the security and reliability of transactions in Islamic financial institutions. The findings will highlight various factors influencing public perception, including personal experiences, knowledge of Islamic financial products, and the level of trust in banks. Practical Implication - The research findings are expected to contribute valuable insights into the factors influencing public perceptions of Islamic financial services. The findings enhance the existing literature by framing trust as both a behavioral factor and a strategic resource, in line with global frameworks such as ESG (Governance dimension) and SDGs (Decent Work and Economic Growth, Reduced Inequalities). Originality/value - This study provides practical insights for Islamic banks to enhance transparency, security measures, and ethical standards, thereby strengthening their position as inclusive and resilient financial institutions within Muslim and multicultural communities